THE CHANGING PERCEPTION OF THE ENVIRONMENT IN RELATION TO THE ARTISTIC PRACTICES - Naseem, Bushra (International Journal of Psychosocial Rehabilitation, 2020)
This paper analyzes the work of artists who are creating their work in nature using elements of art from nature. It addresses the wide horizon and diverse approaches of the artists towards changing perceptions related to the artistic practices. Their aim is to work in harmony with nature so much so that they have used the elements of nature to treat their artwork. Very essential outside material is also used, but the material should be environmentally friendly. The mesmerizing installations, though mostly ephemeral, not only beautify nature but are also provocative and insightful. The field of environmental art is as diverse as the natural world that inspires it.